Invasive measurement of hepatic venous pressure gradient before resection of hepatocellular carcinoma - Hříbek, Petr; Klasová, Johana; Tůma, Tomáš; Pudil, Jiří; Menclová, Kateřina; Mačinga, Tomáš; Kubala, Eugen; Urbánek, Petr (Clinical and experimental hepatology, 2023)
AIM OF THE STUDY: To evaluate the role of hepatic venous pressure gradient (HVPG) measurement in patients with resectable hepatocellular carcinoma (HCC) we describe our experience with the procedure as part of our hospital standard preoperative algorithm. We present our protocol for this situation, the HVPG measurement procedure, and the results of our cohort. MATERIAL AND METHODS: We performed a retrospective statistical analysis of all patients who underwent planned hepatic resection for HCC with HVPG measurement between 1/2016 and 1/2023. The cohort included 35 patients (30 males, mean age 69.5 years) who underwent HVPG measurement before liver resection for HCC. RESULTS: The success rate of measurement was 91.4%, with serious complications in 2.9% of cases. Due to the clinically significant portal hypertension (CSPH) 31.3% of patients were rejected for resection. Seventeen patients with excluded CSPH underwent resection with one case of a postoperative liver event, liver decompensation, representing 5.9% of them. One patient (5.9%) had a complicated postoperative course with fasciitis. None of the patients who underwent resection (88.2%) was readmitted to the hospital due to surgical complications or a liver event during 90 days of follow-up, and no death was reported. The median overall survival (OS) in the resected subgroup was 70 months (95% CI: 52-86), and in patients rejected for surgery (resection and transplantation) 35 months (95% CI: 13-48). CONCLUSIONS: HVPG measurement is the gold standard for the quantification of portal hypertension. Hepatic vein catheterization is invasive, but a safe procedure, with a clear impact on the management of resectable HCC.
Keywords: cirrhosis; hepatocellular carcinoma; HVPG; portal hypertension; liver resection